English Teacher Obstacle on Implementing the 2013 Curriculum - Martina Napratilora; Nova Adi Kurniawan; Seri Yanti Siagian (Indonesian Journal of Learning Education and Counseling, 2019)
Abstract. This study aim is to explain how to implement the 2013 curriculum to teach English and describe English teacher obstacle on the curriculum implementation. The research method is a library study. The research finding shows that the English teachers are not able to apply 2013 curriculum well in the class. They get confused to use it in teaching and learning process, they are not able to apply the scientific approach in teaching and learning process well too. It because the teacher has a lack of knowledge about the 2013 curriculum itself and the scientific approach is a new approach in teaching and learning English. So, the implementation of the 2013 curriculum is not maximum especially in applying the scientific approach to the class. In analyzing the data, the writer uses content analyzes technique. Therefore, the English teacher has to learn and work hard to handle the obstacle in implementing the 2013 curriculum well like the following more socialization, more workshops of 2013 curriculum and also need support from the stakeholders like government, the Ministry of Education and Culture, Headmaster, and so on in realizing 2013 curriculum. Keywords: Implementing, 2013 curriculum, English teacher.